Microstructures and the Mechanical Properties of the Al–Li–Cu Alloy Strengthened by the Combined Use of Accumulative Roll Bonding and Aging. Issue 1 (23rd August 2019) - Tang, Yongpeng; Hirosawa, Shoichi; Saikawa, Seiji; Matsuda, Kenji; Lee, Seungwon; Horita, Zenji; Terada, Daisuke
Abstract : Herein, the age‐hardening behavior of the severely deformed and then artificially aged A2099 Al–Li–Cu alloy is investigated by Vickers hardness test, tensile test, and transmission electron microscopy (TEM). The combined processes of accumulative roll bonding (ARB) and aging treatment at 373 K for 2419 ks result in the highest hardness (≈190 HV) for the 5‐cycled ARB sample with an age hardenability of 37 ± 2 HV. For the 2‐cycled ARB sample with aging treatment, the ultimate tensile strength and elongation to failure reach 553 MPa and 7%, which are greater than those of the ARB sample without aging treatment (i.e., 442 MPa and 1%). The corresponding TEM microstructures suggest that the refined δ′ –Al3 Li particles formed by spinodal decomposition are responsible not only for higher hardness and strength but also for the optimized strength–ductility balance. Therefore, our proposed strategy, i.e., "take advantage of spinodal decomposition, " is regarded as a convincing approach to induce nanosized precipitates within ultrafine grains for optimizing the strength–ductility balance. Abstract : The age‐hardening behavior of the severely deformed and then artificially aged A2099 Al–Li–Cu alloy is investigated. The refined δ ′ –Al3 Li particles formed by spinodal decomposition are responsible not only for higher hardness and strength but also for the optimized strength–ductility balance in the 2‐cycled accumulative roll bonding (ARB) sample with ultimate tensile strength and elongation to failure reaching 553 MPa and 7%.